2021
DOI: 10.1109/access.2021.3128668
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Immunosensor Platform Using Low-Cost ENIG PCB Finish Electrodes: Application for SARS-CoV-2 Spike Protein Sensing

Abstract: In recent years, lab-on-chip systems based on printed circuit board (PCB) substrates are gaining attraction primarily due to their low cost of manufacturing. Adapting inexpensive PCBs for development of immunosensors usually requires additional processing steps such as gold electroplating and electropolymerisation, that add to the manufacturing costs. In this work, we demonstrate methods to leverage electroless nickel immersion gold (ENIG) finish PCBs as electrodes for developing electrochemical immunosensors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 56 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…The ENIG PCB electrode specifications are detailed in our previous work 11 . Conventional cleaning recipes for electrodes, such as using piranha solution or cyclic voltammetry with sulphuric acid are not recommended for ENIG PCB electrodes, as they may cause stripping of the thin gold layer (thickness ) and expose the underlying copper layer that is susceptible to corrosion 21 25 . The electrodes were therefore cleaned using lint-free wipes dampened with IPA.…”
Section: Methodsmentioning
confidence: 99%
“…The ENIG PCB electrode specifications are detailed in our previous work 11 . Conventional cleaning recipes for electrodes, such as using piranha solution or cyclic voltammetry with sulphuric acid are not recommended for ENIG PCB electrodes, as they may cause stripping of the thin gold layer (thickness ) and expose the underlying copper layer that is susceptible to corrosion 21 25 . The electrodes were therefore cleaned using lint-free wipes dampened with IPA.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, SARS-CoV-2 spike protein (SP) in PBS and in artificial saliva samples was detected on screen-printed electrodes with working electrode (WE, Ø = 3 mm) modified with AuNPs (70–100 nm). It is reported that electrodes cleaned with base piranha (AC) solution provided more intense DPV electrochemical signals and were used for biofunctionalization steps with Cys/GA/anti-spike (10 × 10 6 pg/mL antibody, 12 µL drop casted) that made the detection of 0.1 × 10 3 to 500 × 10 3 pg/mL spike protein possible ( Figure 3 ) [ 52 ].…”
Section: Electrochemical Immunosensorsmentioning
confidence: 99%
“…Moreover, the devices described in References [ 186 , 187 ] used both gold and silver PCB-based electrodes. Finally, the PCB-based gold electrodes fabricated using the standard ENIG plating process have been applied to the electrochemical sensing of SARS-CoV-2 amplicons and spike protein [ 188 , 189 ]. As can be seen, the copper, gold and silver layers of the PCB are a good choice for developing biosensors.…”
Section: Printed Circuit Boards For Biomedical Applicationsmentioning
confidence: 99%